Multicultural Education in Islamic Boarding School - Sakinatul Birroh; Haryono Haryono; Yuli Utanto (Universitas Negeri Semarang, 2022)
Indonesia is a great nation with various differences. This has the potential to occur conflicts. Through multicultural-based education in Pesantren can prevent conflicts. The main objective of this study is to describe the concept of multicultural education in Islamic boarding schools and describe the implementation of multicultural education in Islamic boarding schools. This research uses qualitative phenomenological methods with data collection techniques through observation, interviews, and documentation. The results of the study found that the concept of multicultural education is an educational education that providing an understanding of equality, freedom, tolerance, and respect for the differences and diversity that exist in Indonesia and even in the world, ranging from physical forms, languages, tribes, races, customs, cultures, to beliefs in religion, based on religious knowledge and general knowledge, so that one another can coexist in harmony and peace. Its implementation, there is equality and freedom in all students, there are teaching materials with multicultural educational materials in Islam, and leadership education is given with material on national insight, there is art and cultural education. This research can be considered by local and central governments in deciding policies related to Islamic boarding school education and formal education and become a reference to overcome and prevent conflicts in society caused by various differences.